Protocol for collaboration between national and community seedbanks (guideline) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
This guideline is a generic collaboration protocol to formalize the collaboration between a national genebank and community seed banks, outlining principles, good practices and areas of collaboration.